System of heterogeneous data transmission on the basis of a self-regulation network with an option of retransmission - Narimanova, G.N.; Inkina, M.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article discusses structural features of wireless data transmission technologies. Based on client-server architecture, a data transmission algorithm has been developed. This algorithm includes the possibility to retransmit with automatic search for the optimal path. A system of heterogeneous data transmission is proposed, which ensures high efficiency of remote data collection and transmission under the conditions of intensive interference. The data transmission system provides automatic selection of the optimal data transmission path.
Keywords: wireless technology; data transmission; heterogeneity; retransmission